Response of root anatomy and vitamin C content of Brassica juncea L. on biofertilizer application in a saline environment - Palupi, Dwi Rekno; Siswanti, Dwi Umi (Biogenesis: Jurnal Ilmiah Biologi, 2023)
Indian mustard (Brassica juncea L.) is part of the family Brassicaceae which has an annual-herbaceous habitus and is counted as a popular vegetable commodity in Indonesia so it has a high-demand market. To fulfill the demand market can be done by hydroponic cultivation and biofertilizer application. Application of biofertilizer which contains inoculant microorganisms can support plant growth with increased availability of nutrients in planting medium and neutralized salinity stress effect. Salinity stress is indicated by the high concentration of Na+ and Cl- ions in plants resulting in toxicity and osmotic stress which will inhibit plant growth. This study aimed to determine the effect of various dosages of biofertilizer on plant growth and productivity with plant height, leaf number, cortex thickness, metaxylem diameter, and ascorbic acid levels as parameters. This research used cow urine base biofertilizer containing nitrogen (N), phosphate (P), kalium (K), and calcium (Ca). There are a few treatments: negative control, positive control, biofertilizer treatment 40 mL, 80 mL, and 120 mL dosage, and salinity treatment by applying NaCl 5000 ppm 10 mL/system. As the result showed on 120 mL biofertilizer dosage has the highest mean of plant height and leaves number, and 80 ml biofertilizer dosage treatment has the highest average of cortex thickness and metaxylem diameter, but the various dosage of biofertilizer treatment did not have a significant effect on ascorbic acid levels increase. Growth in plants given biofertilizer is higher than the plant growth that grew in the negative control treatment. It can be concluded that the application of biofertilizer can support the growth of B. juncea L. in the hydroponic system under salinity stress.